2010
DOI: 10.1016/s0828-282x(10)70438-4
|View full text |Cite
|
Sign up to set email alerts
|

Administrative data have high variation in validity for recording heart failure

Abstract: H eart failure (HF) has been widely studied because of its high mortality and morbidity rates (1-4). Studies on HF have relied on multiple data sources such as surveys, disease registries, hospital charts and administrative data. Of these sources, administrative data have been increasingly used for health services utilization and outcome evaluation.Administrative data result from implementing health care delivery, enrolling members into health insurance plans and reimbursing health care providers for services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 33 publications
6
91
0
2
Order By: Relevance
“…11,12 In turn, the use of such databases for research purposes also presents some potential limitations relating to the accuracy and validity of the coding of diagnoses. [13][14][15] Other limitations of this study include the fact that, although hospital level of care and hospital volume were known for each delivery year, data on hospital services were only available for the year 2001 and were extrapolated to the other years in which individual-level data were available. Future studies should therefore focus on the more precise evaluation of these hospital services, as their presence or absence may vary over time, in addition to other potential hospital characteristics that may affect neonatal outcomes, such as the 24-h availability of obstetrical anesthesia services and in-house obstetrical services.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In turn, the use of such databases for research purposes also presents some potential limitations relating to the accuracy and validity of the coding of diagnoses. [13][14][15] Other limitations of this study include the fact that, although hospital level of care and hospital volume were known for each delivery year, data on hospital services were only available for the year 2001 and were extrapolated to the other years in which individual-level data were available. Future studies should therefore focus on the more precise evaluation of these hospital services, as their presence or absence may vary over time, in addition to other potential hospital characteristics that may affect neonatal outcomes, such as the 24-h availability of obstetrical anesthesia services and in-house obstetrical services.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have shown that administrative data can fail to identify all eligible patients, may miss care delivered, and may overlook justifications for care deferral. [4][5][6][7][8] In a recent study, researchers identified documented reasons for not pursuing recommended therapy in charts of 43% of randomly selected patients with coronary artery disease whose care did not meet a quality measure. 8 Although concerns are often levied that administrative data may underestimate health care quality, [9][10][11] there is little information on the extent to which patient preferences or medical contraindications affect variation in reported performance.…”
Section: Introductionmentioning
confidence: 99%
“…Articles were excluded for various reasons: the data source under review was not an electronic administrative database (e.g., medical charts), [18][19][20] the data were not from Canada, 21,22 or the article was a summary of other literature. 23,24 Four articles were excluded because the abstract and article were not published in English (two in French, one in Spanish and one in German). A total of 156 publications were retained, of which 144 (92.3%) were peerreviewed publications and 12 (7.7%) were non-peer-reviewed publications (see Supplementary Table 1 in the ARTICLE TOOLS section on the journal site).…”
Section: Synthesismentioning
confidence: 99%